Age-Associated Changes in the Vascular Renin-Angiotensin System in Mice. (20th April 2016) - Yoon, Hye Eun; Kim, Eun Nim; Kim, Min Young; Lim, Ji Hee; Jang, In-Ae; Ban, Tae Hyun; Shin, Seok Joon; Park, Cheol Whee; Chang, Yoon Sik; Choi, Bum Soon
Abstract : Background . This study evaluated whether the change in the renin-angiotensin system (RAS) is associated with arterial aging in mice. Methods . Histologic changes and expressions of transforming growth factor- β (TGF- β ), collagen IV, fibronectin, angiotensin II (Ang II), angiotensin-converting enzyme (ACE), angiotensin-converting enzyme 2 (ACE2), angiotensin II type 1 receptor (AT1R), angiotensin II type 2 receptor (AT2R), prorenin receptor (PRR), Mas receptor (MasR), endothelial nitric oxide synthase (eNOS), NADPH oxidase 2 and oxidase 4 (Nox2 and Nox4), 8-hydroxy-2′-deoxyguanosine (8-OHdG), 3-nitrotyrosine, and superoxide dismutase 1 and dismutase 2 (SOD1 and SOD2) were measured in the thoracic aortas from 2-month-old, 12-month-old, and 24-month-old C57/BL6 mice. Results . Twenty-four-month-old mice showed significantly increased aortic media thickness and expressions of TGF- β, collagen IV, and fibronectin, compared to 2-month-old and 12-month-old mice. The expressions of PRR, ACE, and Ang II, and AT1R-positive area significantly increased, whereas expressions of ACE2 and MasR and AT2R-positive area decreased with age. The expressions of phosphorylated serine 1177 -eNOS, SOD1, and SOD2 decreased, and the 8-OHdG-positive area and the 3-nitrotyrosine-positive area increased with age. The expression of Nox2 significantly increased with age, but that of Nox4 did not change. Conclusions . The enhanced PRR-ACE-Ang II-AT1R axis and reduced ACE2-MasR axis were associated with arterial aging in mice.